Smart Card with Audio Connection to Improve Tooth Brushing Skills for Visually Impaired Children in SLB Negeri Jepara - Evi Adawiyyah; Endah Aryati Eko Ningtyas; Bedjo Santoso (Poltekkes Kemenkes Semarang, 2024)
Visual impairment can lead to challenges in maintaining oral hygiene for visually impaired people. Individuals with visual impairment have a higher risk of experiencing oral health problems compared to those with normal vision. This limitation is one of the inhibiting factors for blind people in obtaining knowledge about oral health, which in turn will affect their attitudes and actions in maintaining oral hygiene. The sensitivity of blind children is in one of their senses, namely sensitivity to sound through their hearing. Based on these problems, an innovation was made in the form of Smart Card With Audio Connection media to improve the teeth brushing skills of blind children. In the implementation of this activity, through several stages, namely the preparation stage (including licensing and preparation of officers), the implementation stage (pretest of tooth brushing skills and dental hygiene status, training to teachers, and simulation of brushing teeth using Smart Card with Audio Connection), and the evaluation stage (including post test of tooth brushing skills and dental hygiene status). This activity is 17 blind children in SLB Negeri Jepara. The results of the activity show that the Smart Card With Audio Connection Model is effective in improving the teeth brushing skills and dental hygiene status of visually impaired children.